Precipitation of Radiation Belt Electrons by EMIC Waves With Conjugated Observations of NOAA and Van Allen Satellites - Zhigang Yuan; Kun Liu; Xiongdong Yu; Fei Yao; Shiyong Huang; Dedong Wang; Zhihai Ouyang (Geophysical Research Letters)
Abstract In this letter, we present unique conjugated satellite observations of MeV relativistic electron precipitation caused by electromagnetic ion cyclotron (EMIC) waves. On the outer boundary of the plasmasphere, the Van Allen probe observed EMIC waves. At ionospheric altitudes, the National Oceanic and Atmospheric Administration (NOAA) 16 satellite at the footprint of Van Allen probe simultaneously detected obvious flux enhancements for precipitating >MeV radiation belt electrons but not for precipitating <MeV electrons. Theoretical calculations of pitch angle diffusion coefficients for radiation belt electrons indicate that observed EMIC waves can solely lead to flux enhancements of precipitating >MeV radiation belt electrons. Our result provides a direct magnetic conjugated observational link between in situ inner magnetospheric EMIC waves and precipitation of MeV relativistic electrons at ionospheric altitudes so as to reveal that EMIC waves can solely scatter MeV radiation belt electrons into the loss cone so as to precipitate into the atmosphere.